2008
DOI: 10.1007/s11547-008-0227-z
|View full text |Cite
|
Sign up to set email alerts
|

E-learning tools for education: regulatory aspects, current applications in radiology and future prospects

Abstract: The increasing diffusion of continuous education will reduce the costs of e-learning and make this training method, which helps keep pace with technological progress, more attractive, with significant professional gains for radiologists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
6

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 11 publications
1
43
0
6
Order By: Relevance
“…This agrees with previous research that noted the need for training to allow academics to become familiar with new technology prior to its implementation in examinations (Pinto et al, 2008). The findings from the current study indicated that the use of technology was associated with concerns about the reliability of "the system" and apprehension about losing data, selection of the correct student, saving and storing the correct data for each student, and about the potential for the system to shut down during an examination.…”
Section: Challenges With Implementationsupporting
confidence: 88%
“…This agrees with previous research that noted the need for training to allow academics to become familiar with new technology prior to its implementation in examinations (Pinto et al, 2008). The findings from the current study indicated that the use of technology was associated with concerns about the reliability of "the system" and apprehension about losing data, selection of the correct student, saving and storing the correct data for each student, and about the potential for the system to shut down during an examination.…”
Section: Challenges With Implementationsupporting
confidence: 88%
“…Actions directed to this training modality are found in some areas of health, especially in nursing (Campbell et al, 2008;Edwards, 2005;Holtslander et al, 2012;Teles Filho & Cassiani, 2008;Xelegati & Evora, 2011), and in some specialties of medicine (Gardella et al, 2003;Llambí et al, 2007;Pinto et al, 2008;VanLue et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Reports on distance learning are found in literature in the medicine field (Gardella, Guarin, & Vive, 2003;Llambí et al, 2007;Pinto et al, 2008;VanLue et al, 2007) and, mainly, in the nursing field (Campbell, Gibson, Hall, Richards, & Callery, 2008;Edwards, 2005;Holtslander, Racine, Furniss, Burles, & Turner, 2012;Teles Filho & Cassiani, 2008;Xelegati & Evora, 2011). The quality of the service of tele-education and tele-assistance has been proved by different authors (Eskenazi, Martins, & Ferreira, 2013;Hersh, Junium, Mailhot, & Tidmarsh, 2001;Rafiq & Merrell, 2005;Roine, Ohinmaa, & Hailey, 2001;Shaikh, Lehmann, Kaleida, & Cohen, 2008;Vucković et al, 2003); however, the cost-effectiveness relation still deserves investigation (Soirefmann, Blom, Leopoldo, & Cestari, 2008).…”
Section: Overview Of Distance Learningmentioning
confidence: 99%
“…We believe that surgeon-to-surgeon communication is the most important, the easiest, most closely related to clinical practice, and cost-effective method of patient-problem-oriented CME. A number of evaluation studies have examined the effectiveness of Webbased CME [6,10,15,32,40]. One web-based CME instructional format comprising multimedia-enhanced learning tutorials supplemented by asynchronous computermediated conferencing for case-based discussions was reportedly effective in enhancing knowledge, confidence, and self-reported practice change outcomes across a variety of clinical subject matter areas [6].…”
Section: Introductionmentioning
confidence: 99%
“…Appropriately designed, evidence-based online CME can produce objectively measured changes in behavior as well as sustained gains in knowledge that are comparable or superior to those realized from effective live activities [10]. Pinto et al [32] performed a PubMed search focused on e-learning tools and applications in the health sector, with specific reference to radiology, and concluded that increasing the volume of continuous education will reduce the costs of e-learning and make this training method, which helps keep pace with technological progress, more attractive, with substantial professional gains for radiologists. Karlinsky et al [15] reported use of effective videoconferencing and online learning activities increases access to quality CME related to workplace injury management.…”
Section: Introductionmentioning
confidence: 99%